Survei Status Gizi Siswa SMK Negeri 3 Palangka Raya - Abeng, Andi Tenri; Idris, Muhammad (Jurnal Keolahragaan JUARA, 2021)
Health issues are very important issues and are always a topic of conversation. Health is the most important thing in supporting human life. Health problems are often underestimated by people for temporary pleasure, especially in teenagers. Changes that run very fast in body shape cause teenagers to be in an unstable emotional condition, so that teenagers tend to do things without calculation, including unhealthy behavior because of the individual's desire to be accepted by his friends. class X SMK Negeri 3 Palangka Raya. This research was conducted at SMK Negeri 3 Palangka Raya. The research population was 315 students with a sample of 97 students using random sampling. This research is a quantitative descriptive study using a survey method. Data collection techniques used anthropometric measurements which included measurements of weight and height and then calculated based on data analysis techniques using quantitative des criptive with percentages. The results showed that the nutritional status of class X students of SMK Negeri 3 Palangka Raya was in the thin category of 5 students (6.3 %), normal category of 59 students (74.6%), and obese category of 15 students (19%). So it can be concluded that the nutritional status of class X students of SMK Negeri 3 Palangka Raya is normal.